INFORMATION OF MEDICINE’S INVENTORY SYSTEM AT PUSKESMAS TELUKNAGA - Christien Setiya Kesumawati; Padeli Padeli; Amal Awallya (UNIVERSITAS RAHARJA, 2018)
Puskesmas Teluknaga is one of puskesmas with a lot of patients, each day can reach 100-150 patients. Therefore, the service to treat all the patients must be done quickly so that the patients have no complaints. While in medicines area, the information system is stil using a simple method by using manual record in the book / paper. To save the administration reports, pharmacies and warehouses rely solely on Microsoft excel applications. Manual data consists of many datas. In addition, the file storage for manual data can be damaged. Therefore the author created a strategy in developing the information systems of data processing to assist the process of making medicine reports. To obtain an effective and efficient information system, the system was designed in the Final Report entitled